The definition of non-dimensional integration temperature difference and its effect on organic Rankine cycle. (1st April 2016) - Yang, Xufei; Xu, Jinliang; Miao, Zheng; Zou, Jinghuang; Qi, Fengliang
Highlights: Two non-dimensional integration temperature differences are newly defined. Integration temperature differences are experimentally determined. The first non-dimensional temperature difference is linear to the specific exergy losses. Performance parameters reach maximum at a specific integration temperature difference. Integration temperature difference guides engineers to optimize the ORC system. Abstract: The integration temperature difference Δ T i considers the heat transfer routes, linking the heat transfer process with the thermodynamic behavior of heat exchangers. The first and second non-dimensional integration temperature differences are defined as Δ T i, h ∗ = Δ T i / T h, i and Δ T i, s ∗ = Δ T i / ( T h, i - T 0 ) respectively, where T h, i is the heat source temperature and T 0 is the environment temperature. This paper is the first to experimentally verify the significance of the non-dimensional integration temperature differences on organic Rankine cycle (ORC) systems. The first non-dimensional temperature difference is shown to have linear relationship with the revised entropy generation numbers ( Ns ). With increases of the second non-dimensional integration temperature difference, the expander powers, system thermal and exergy efficiencies had parabola distributions. They simultaneously reached maximum at Δ T i, s ∗ = 0.282, under which the vapor cavitation in the expander disappears and the exergy losses of heat exchangers are acceptable to elevate the expander efficiency. Beyond the optimal point, the ORC performance is worsened either due to the vapor cavitation in the expander, or due to the poor thermal matches in the evaporator and condenser. The second non-dimensional integration temperature difference comprehensively reflects the effects of heat source temperatures, heating powers and organic fluid flow rates and pressures, etc. It balances exergy destructions of various components to optimize the system. Thus, it can be an important parameter index to maximize the power or electricity output for a specific heat source. The usefulness of the integration temperature difference and the future work are discussed in the end of this paper.